Flexible Work Arrangements: A Bibliometric Review - Loso Judijanto (West Science Interdisciplinary Studies, 2026)
This study presents a comprehensive bibliometric analysis of Flexible Work Arrangements (FWAs) to explore the intellectual structure, research trends, and thematic evolution within the field. Using data retrieved from the Scopus database covering the period 2000–2026, this study applies bibliometric techniques including co-authorship, citation analysis, keyword co-occurrence, and visualization using VOSviewer. The findings reveal a significant increase in FWA-related publications, particularly after the COVID-19 pandemic, indicating the growing importance of flexible work in contemporary organizational contexts. The results identify key research clusters centered on work–life balance, job satisfaction, employee well-being, and remote work practices. Additionally, the analysis highlights the dominance of developed countries such as the United States and China in knowledge production, while emerging economies show increasing participation. The thematic evolution demonstrates a shift from traditional human resource management perspectives toward multidisciplinary approaches incorporating digital transformation, mental health, and workplace sustainability. This study contributes to the literature by providing a structured overview of FWA research, identifying influential contributions, and highlighting future research directions, particularly in cross-cultural and long-term organizational impacts of flexible work systems.